Analisis Faktor Determinasi Pembelian Kosmetik Halal - Nur Halima; Lailatul Qodariyah; Sarkawi Sarkawi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research aims to determine the factors that influence the purchase of halal cosmetics. This research was conducted using quantitative methods using Multiple Linear Regression analysis. The results of this research state that price and quality variables have no influence on the decision to purchase halal cosmetics by mahasantri at the IDIA Al-Amien Islamic boarding school and Mambaul Ulum Bata-Bata Islamic boarding school, while social variables and religiosity variables have a significant effect on the decision to purchase halal cosmetics by mahasantri which is at the IDIA Al-Amien Islamic boarding school and the Mambaul Ulum Bata-Bata Islamic boarding school.